Pengaruh Kualitas Pelayanan dan Citra Destobasi terhadap Loyalitas Pengunjung Wisata Mangrove dengan Kepuasan Wisatawan sebagai Variabel Intervening - Lutfiyah, Zekiyatul; AS, Fathor (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to identify the effect of service quality variables and destination image on tourist loyalty through tourist satisfaction. the research approach used is quantitative causality, with the research population being all visitors to labuhan madura mangrove tourism, the sample size is 112 respondents and the sampling technique used is purposive sampling. this research was collected by distributing questionnaires and the results will be analyzed using the Partial Least Square (PLS) method. The results stated that service quality has a positive and significant effect on tourist loyalty, service quality has a positive but insignificant effect on tourist satisfaction, destination image has a positive and significant effect on tourist loyalty, destination image has a positive and significant effect on tourist satisfaction, and tourist satisfaction has a positive and significant effect on tourist loyalty. Keywords: Service Quality, Destination Image, Satisfaction, And Loyalty.